2019
DOI: 10.1093/jn/nxy299
|View full text |Cite
|
Sign up to set email alerts
|

Strong Multivariate Relations Exist Among Milk, Oral, and Fecal Microbiomes in Mother-Infant Dyads During the First Six Months Postpartum

Abstract: Background Neonatal gastrointestinal (GI) bacterial community structure may be related to bacterial communities of the mother, including those of her milk. However, very little is known about the diversity in and relationships among complex bacterial communities in mother-infant dyads. Objective Our primary objective was to assess whether microbiomes of milk are associated with those of oral and fecal samples of healthy lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
92
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 70 publications
14
92
2
3
Order By: Relevance
“…With milk now being regarded as an inoculum for the infant GIT, the existence of an enteromammary route has been explored. Although milk and maternal feces microbiota are distinct, a strong correlation has been reported between them (Williams et al, 2019). The isolation of a common strain of the obligate anaerobe Bifidobacterium longum from maternal and neonate feces as well as from milk supports the hypothesis of an enteromammary route (Jost et al, 2014).…”
Section: Origins Of Milk Microbial Communitymentioning
confidence: 75%
See 3 more Smart Citations
“…With milk now being regarded as an inoculum for the infant GIT, the existence of an enteromammary route has been explored. Although milk and maternal feces microbiota are distinct, a strong correlation has been reported between them (Williams et al, 2019). The isolation of a common strain of the obligate anaerobe Bifidobacterium longum from maternal and neonate feces as well as from milk supports the hypothesis of an enteromammary route (Jost et al, 2014).…”
Section: Origins Of Milk Microbial Communitymentioning
confidence: 75%
“…Shared genera between mother's milk and infant feces accounted for 70-88% of the relative abundance of fecal microbiota (Murphy et al, 2017). Contribution of milk microbiota to infant gastrointestinal microbiota was also pointed out by Williams et al (2019), who estimated a direct contribution of ∼4.9% and suggested additional contribution through a probable effect on the microbiota present in the stomach, small intestine, and upper large intestine. Likewise, in a metagenomic study, Pärnänen et al (2018) reported that 76% of the species found in milk were present in the infant's GIT.…”
Section: The Milk Microbiota and Infant Healthmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, bacteria from breast milk could be influenced by the infant oral cavity, where studies have reported, via ultrasound imaging, retrograde back flow of milk due to infant suckling. This back flow of milk into the mammary ducts provides one possible mechanism detailing the transfer of bacteria from infant's mouth into the mother's mammary gland [214][215][216]. Additionally, it was suggested that breast pump expression could influence the microbiome, proposing the pump could play a potential role in retrograde of exogenous bacteria into the milk ducts [217,218].…”
Section: Origins Of Milk Microbiomementioning
confidence: 99%